PENGARUH TEKNOLOGI INFORMASI DAN SALING KETERGANTUNGAN TERHADAP KINERJA MANAJERIAL DENGAN KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN SEBAGAI VARIABEL INTERVENING - Sumolang, Jerry Hans; Desmiyawati, Desmiyawati; Rofika, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This major study of management accounting was applied to the contingency approach to studying management accounting system design and performance. This study examined the effect of information technology and the interdependence of managerial performance through management accounting systems. Information technology is a merger between computer technology and telecommunications. While the interdependence it self is one of the contingency variable to consider in designing the SAM. While managerial performance is a measure of how effective and efficient performance of individual members of the organization. Managerial performance is one of the factor that can improve organizational effectiveness. The population used in this study is a manager of banking services at Riau Province. Study sample 60 respondents selected based on criteria in purposive sampling. Data were analyzed using Partial Least Square (PLS) in a of Structural Equation Modeling (SEM). The results shows that the information technology (TI) have indirect effect on managerial performance through management accounting system (SAM). Interdependence (SK) also have indirect effect on managerial performance through management accounting system (SAM).Keywords : Information Technology, Interdependence, Management Accounting System (MAS), Managerial Performance.